Electrodynamic analysis of materials for the antenna elements. Issue 2 (November 2018) - Chabanenko, Alexandr; Frolova, Elena; Balashov, Victor; Smirnova, Maria
Abstract: The electrodynamic problem of electromagnetic field propagation in a two-layer dielectric structure has been set and solved. A constructive solution is proposed for controlling the propagation conditions of a surface wave in the wall of a controlled radiant cone or antenna cover by introducing an additional dielectric layer between the fairing wall and the contact radiator.